Fire and ice - Hunter, Erin. (New York : HarperCollins, 2003)
Fireheart, a full-fledged warrior cat, must confront questions of loyalty and identity as he faces the possibility of betrayal from within his own forest clan.
Booklist, September 2003.
Voice of Youth Advocates (V.O.Y.A.), August 2003.
Kirkus Review, May 2003.
5.4.
5-8.
810L
Keywords: Cats -- Fiction; Fantasy; Cats -- Fiction; Fantasy fiction; Cats -- Fiction; Fantasy